Combined heterogeneous distribution of salt and aroma in food enhances salt perception. Issue 5 (13th May 2015) - Emorine, Marion; Septier, Chantal; Andriot, Isabelle; Martin, Christophe; Salles, Christian; Thomas-Danguin, Thierry
<x xml:space="preserve">Abstract</x> Combining salt and aroma heterogeneous distribution in hot snacks improves saltiness perception and helps to maintain consumer liking. This approach is relevant for lowering salt content in food.